A distinct cardiopharyngeal mesoderm genetic hierarchy establishes antero-posterior patterning of esophagus striated muscle - Comai, Glenda; Heude, Eglantine; Mella, Sebastian; Paisant, Sylvain; Pala, Francesca; Gallardo, Mirialys; Langa, Francina; Kardon, Gabrielle; Gopalakrishnan, Swetha; Tajbakhsh, Shahragim (eLife, 2019)
In most vertebrates, the upper digestive tract is composed of muscularized jaws linked to the esophagus that permits food ingestion and swallowing. Masticatory and esophagus striated muscles (ESM) share a common cardiopharyngeal mesoderm (CPM) origin, however ESM are unusual among striated muscles as they are established in the absence of a primary skeletal muscle scaffold. Using mouse chimeras, we show that the transcription factors Tbx1 and Isl1 are required cell-autonomously for myogenic specification of ESM progenitors. Further, genetic loss-of-function and pharmacological studies point to MET/HGF signaling for antero-posterior migration of esophagus muscle progenitors, where Hgf ligand is expressed in adjacent smooth muscle cells. These observations highlight the functional relevance of a smooth and striated muscle progenitor dialogue for ESM patterning. Our findings establish a Tbx1-Isl1-Met genetic hierarchy that uniquely regulates esophagus myogenesis and identify distinct genetic signatures that can be used as framework to interpret pathologies arising within CPM derivatives.
Keywords: cardiopharyngeal mesoderm; esophagus striated muscles; Tbx1-Isl1-Met/HGF; myogenic migration; antero-posterior patterning